2021
DOI: 10.5194/hess-25-603-2021
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of kernel-based versus ANN and deep learning methods in monthly reference evapotranspiration estimation

Abstract: Abstract. Timely and accurate estimation of reference evapotranspiration (ET0) is indispensable for agricultural water management for efficient water use. This study aims to estimate the amount of ET0 with machine learning approaches by using minimum meteorological parameters in the Corum region, which has an arid and semi-arid climate and is regarded as an important agricultural centre of Turkey. In this context, monthly averages of meteorological variables, i.e. maximum and minimum temperature; sunshine dura… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(25 citation statements)
references
References 38 publications
1
23
0
1
Order By: Relevance
“…Zhao et al (2019) [46] developed a method for post-processing seasonal GCM outputs to predict monthly and seasonal RET. Several models on heuristic and fuzzy-logic science for estimations of PE and RET and machine learning algorithms such as combined neural networks, genetic algorithm model, linear genetic programming, fuzzy genetic, adaptive neuro-fuzzy inference system, artificial neural networks, multilayer perceptron neural network, co-active neuro-fuzzy inference system, radial basis neural network and self-organizing map neural network showed high accuracy in different climate zones [15,[47][48][49][50][51].…”
Section: Developments In Et Measurement and Estimationmentioning
confidence: 99%
“…Zhao et al (2019) [46] developed a method for post-processing seasonal GCM outputs to predict monthly and seasonal RET. Several models on heuristic and fuzzy-logic science for estimations of PE and RET and machine learning algorithms such as combined neural networks, genetic algorithm model, linear genetic programming, fuzzy genetic, adaptive neuro-fuzzy inference system, artificial neural networks, multilayer perceptron neural network, co-active neuro-fuzzy inference system, radial basis neural network and self-organizing map neural network showed high accuracy in different climate zones [15,[47][48][49][50][51].…”
Section: Developments In Et Measurement and Estimationmentioning
confidence: 99%
“…The study concluded that the proposed novel data intelligent model in combination with SVM has outperformed and found best in comparison with the empirical model. Sattari et al (2021) applied five data intelligent machine learning models for estimating ET 0 using several input meteorological combinations and found that combining machine learning (hybrid) models increase predictive ability in results. Malik et al (2019) estimated ET 0 using five machine learning models using different meteorological input combinations and concluded that accuracy in results and efficiency can be increased by using hybrid machine learning models.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that the model with the most inputs resulted in the most accurate predictions of ETo and that tanh was the best activation function in all cases. Sattari et al (2021) tried ten combinations of input variables (from eight to one inputs) [72]. The best performance yielded an R 2 = 0.978.…”
Section: Introductionmentioning
confidence: 99%